Scaling and Confinement in Ultrathin Chalcogenide Films as Exemplified by GeTe. Issue 21 (1st May 2022) - Kerres, Peter; Zhou, Yiming; Vaishnav, Hetal; Raghuwanshi, Mohit; Wang, Jiangjing; Häser, Maria; Pohlmann, Marc; Cheng, Yudong; Schön, Carl‐Friedrich; Jansen, Thomas; Bellin, Christophe; Bürgler, Daniel E.; et al.
Abstract: Chalcogenides such as GeTe, PbTe, Sb2 Te3, and Bi2 Se3 are characterized by an unconventional combination of properties enabling a plethora of applications ranging from thermo‐electrics to phase change materials, topological insulators, and photonic switches. Chalcogenides possess pronounced optical absorption, relatively low effective masses, reasonably high electron mobilities, soft bonds, large bond polarizabilities, and low thermal conductivities. These remarkable characteristics are linked to an unconventional bonding mechanism characterized by a competition between electron delocalization and electron localization. Confinement, that is, the reduction of the sample dimension as realized in thin films should alter this competition and modify chemical bonds and the resulting properties. Here, pronounced changes of optical and vibrational properties are demonstrated for crystalline films of GeTe, while amorphous films of GeTe show no similar thickness dependence. For crystalline films, this thickness dependence persists up to remarkably large thicknesses above 15 nm. X‐ray diffraction and accompanying simulations employing density functional theory relate these changes to thickness dependent structural (Peierls) distortions, due to an increased electron localization between adjacent atoms upon reducing the film thickness. A thickness dependence and hence potential to modify film properties for all chalcogenide films with a similar bonding mechanism is expected. Abstract : In GeTe and related chalcogenides, which all show a unique property portfolio in the crystalline state including strong optical absorption and soft bonds, the thickness dependent properties are explored. A pronounced thickness dependence of the optical and vibrational properties of crystalline GeTe is demonstrated, which is linked to a thickness dependent Peierls distortion, due to an increased electron localization.